Computadores fazem arte, artistas fazem dinheiro: análise da atividade dos desenvolvedores de software - Moita, Dímitre Sampaio (2015)
This work has the general goal to analyze the meaning that developers from software factories attach to their activity. It characterizes the recent transformations of the working world as a historical process of universalization of precarity and aims to confront the promises of immaterial work with the precarious experience of the ICT sector workers. At first, the reason to choose software factories as a research field relied on the concept of taylorization of software production. The use of quality standards within the software factory would result in routinization of activity and deskilling of work. The research applies the social-hermeneutics analysis on the speech collected through semi-structured interviews with six developers. The task of interpreting the meaning contained in the speech is to address the issue of changes in the labor world in light of workers experience. The researcher builds a dialogue involving the speech of developers, other survey data and his own interpretations. Discusses the hypothesis taylorization, considered inaccurate given the experience of respondents, and chooses to discuss the rationalization of software process. The experience of working under the management by projects, highly relevant aspect in the speech of workers, is discussed from two main dimensions, working by projects and working at the client site, which allows to identify more precisely how precarity expresses itself within software factories ambient. Subtle control mechanisms allow the worker self-exploration and hyper-request by the company, which has the precarity as a disciplinary tool that goes beyond the boundaries between life and work.